Negative electrode material for secondary battery, and secondary battery

By using a combination of silicon-containing particles and a phosphate compound cover layer in the negative electrode material of the secondary battery, the problem of silicate phase being eroded by side reactions in the battery is solved, and the cycle characteristics and stability of the battery are significantly improved.

CN119856296APending Publication Date: 2025-04-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380064707.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The silicate phase of the composite particles is easily eroded by side reactions in the secondary battery, resulting in deterioration of the negative electrode material and degradation of the battery cycle characteristics.

Method used

Using a negative electrode material containing silicon particles and a cover layer covered with a phosphate compound, the phosphate compound including anionic phosphate compound, a polyphosphate compound and a metaphosphate compound, is used to protect the silicon particles and inhibit side reactions.

Benefits of technology

It effectively suppresses the reduction of the cycle characteristics of the secondary battery, improves the stability of the negative electrode material and the cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856296A_ABST
    Figure CN119856296A_ABST
Patent Text Reader

Abstract

This negative electrode material for a secondary battery is provided with silicon-containing particles and a coating layer that covers at least a part of the surface of the silicon-containing particles. The silicon-containing particles comprise an ion-conducting phase and a silicon phase dispersed within the ion-conducting phase. The coating layer contains at least one phosphate compound selected from the group consisting of phosphate compounds containing anions represented by general formula (1), polyphosphate compounds, and metaphosphate compounds. In general formula (1), A is an organic group or an oxygen atom. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a negative electrode material for a secondary battery and a secondary battery. Background Art

[0002] Secondary batteries represented by lithium-ion secondary batteries are used as power sources for electronic devices such as portable terminals, power sources for vehicles such as electric vehicles, etc. The negative electrode of the secondary battery uses a negative electrode active material that can absorb and release lithium ions, and graphite is generally used as such a negative electrode active material.

[0003] In recent years, silicon-containing materials having a higher capacity density than graphite have been studied for negative electrode active materials. For example, composite particles having a silicate phase and a silicon phase dispersed in the silicate phase have been studied as materials containing silicon.

[0004] Patent document 1 proposes a negative electrode active material for a secondary battery, which comprises: a silicate phase containing Li, Si and Mx (Mx is an alkali metal, an alkaline earth metal, and an element other than Si); silicon particles dispersed in the aforementioned silicate phase; and metal particles with one or more metals or alloys selected from Fe, Cr, Ni, Mn, Cu, Mo, Zn, and Al as the main component dispersed in the aforementioned silicate phase, wherein the content of each element is 3 to 45 mol% for Li, 40 to 78 mol% for Si, and 1 to 40 mol% for Mx relative to the total amount of elements other than oxygen in the aforementioned silicate phase.

[0005] Patent document 2 proposes a negative electrode active material for a secondary battery, which comprises: a silicate phase containing Li, Si and Mx (Mx is an alkali metal, an alkaline earth metal, and an element other than Si); silicon particles dispersed in the aforementioned silicate phase; and oxide particles dispersed in the aforementioned silicate phase (the oxide particles include: at least any one of oxide particles containing Zr, oxide particles containing Ce, oxide particles containing Ca, oxide particles containing Al, oxide particles containing Fe, oxide particles containing Mg, oxide particles containing Ti and oxide particles containing W), wherein the content of each element relative to the total of elements other than oxygen in the aforementioned silicate phase is 3 to 45 mol% for Li, 40 to 78 mol% for Si, and 1 to 40 mol% for Mx.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2019 / 151016 Pamphlet

[0009] Patent Document 2: International Publication No. 2019 / 151026 Pamphlet Summary of the invention

[0010] Problem that the invention aims to solve

[0011] The silicate phase of the composite particles tends to be gradually corroded due to side reactions occurring in the battery containing the electrolyte. This corrosion leads to degradation of the composite particles and a decrease in the cycle characteristics of the battery.

[0012] Although the negative electrode active materials described in Patent Documents 1 and 2 can suppress particle destruction caused by expansion and contraction of silicon during charge and discharge to a certain extent, they are still not able to sufficiently suppress side reactions.

[0013] Solutions for solving problems

[0014] In view of the above, one aspect of the present disclosure relates to a negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles, wherein the silicon-containing particles include an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase, and the covering layer includes at least one phosphate compound selected from the group consisting of a phosphate compound, a polyphosphate compound, and a metaphosphate compound containing an anion represented by the general formula (1).

[0015]

[0016] In the general formula (1), A is an organic group or an oxygen atom.

[0017] Another aspect of the present disclosure relates to a secondary battery including a positive electrode, a negative electrode, and an electrolyte, wherein the negative electrode includes the negative electrode material for a secondary battery.

[0018] Effects of the Invention

[0019] According to the present disclosure, it is possible to suppress a decrease in the cycle characteristics of a secondary battery.

[0020] The novel features of the present invention are set forth in the appended claims, but both the configuration and content of the present invention, together with other objects and features of the present invention, will be more fully understood from the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a cross-sectional view schematically showing a negative electrode material for a secondary battery according to one embodiment of the present disclosure.

[0022] Figure 2 This is a schematic perspective view in which a portion of a secondary battery according to an embodiment of the present disclosure is cut away. DETAILED DESCRIPTION

[0023] Hereinafter, examples are given to illustrate the embodiments of the present disclosure, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes exemplified, but other numerical values ​​and materials may also be applied as long as the effects of the present disclosure can be obtained. In this specification, the so-called "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read alternatively as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values ​​involving specific physical properties, conditions, etc. are exemplified, as long as the lower limit is not higher than the upper limit, any one of the exemplified lower limits and any one of the exemplified upper limits may be arbitrarily combined. When multiple materials are exemplified, one may be selected and used alone, or two or more may be used in combination.

[0024] In addition, the present disclosure includes a combination of matters described in two or more claims arbitrarily selected from a plurality of claims in the appended claims. That is, matters described in two or more claims arbitrarily selected from a plurality of claims in the appended claims may be combined as long as no technical contradiction occurs.

[0025] (Negative electrode materials for secondary batteries)

[0026] The negative electrode material for a secondary battery of one embodiment of the present disclosure comprises silicon-containing particles (Si-based active material) and a covering layer covering at least a portion of the surface of the silicon-containing particles. The silicon-containing particles include an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase. Hereinafter, the silicon-containing particles are also referred to as "composite particles".

[0027] The coating layer contains at least one phosphate compound selected from the group consisting of phosphate compounds, polyphosphate compounds, and metaphosphate compounds containing an anion represented by the general formula (1).

[0028]

[0029] In the general formula (1), A is an organic group or an oxygen atom.

[0030] The ion-conducting phase may include, for example, at least one selected from the group consisting of a silicate phase, a silicon oxide phase, and a carbon phase. Hereinafter, at least one of the silicate phase and the silicon oxide phase is also referred to as a "silicon compound phase". Composite particles in which a silicon phase is dispersed in a silicate phase are also referred to as "composite particles containing a silicate phase". Composite particles in which a silicon phase is dispersed in a silicon oxide phase are also referred to as "composite particles containing a silicon oxide phase". Composite particles in which a silicon phase is dispersed in a carbon phase are also referred to as "composite particles containing a carbon phase".

[0031] At least a portion of the surface of the composite particles (ion-conducting phase) is covered with a coating layer containing a phosphate compound, thereby protecting the composite particles from the influence of the electrolyte, suppressing side reactions with the electrolyte, and suppressing the corrosion of the ion-conducting phase accompanying the electrolyte. The reduction in the cycle characteristics of the secondary battery caused by the degradation of the composite particles due to the corrosion is suppressed.

[0032] The cycle characteristics are significantly improved by coating the composite particles with the coating layer containing the phosphate compound. The detailed reason is not clear, but it is presumed as follows.

[0033] The above-mentioned phosphate compound includes a plurality of P(=O)O - The phosphate compound can react with the decomposition product of the electrolyte (such as HF) to form a soft polymer on the surface or inside of the covering layer. The covering layer containing such a polymer can easily follow the expansion and contraction of the silicon-containing particles, and the protective effect of the covering layer on the silicon-containing particles can be maintained more firmly during the charge and discharge cycle. In addition, the isolation of particles due to particle rupture can be suppressed.

[0034] The phosphate compound has a plurality of PO structures, has good affinity with water, and is excellent in dispersibility in water. In the wet mixing process of the first step of the negative electrode material preparation method described later, the phosphate compound is dispersed in water and mixed with silicon-containing particles in this state, so that the surface of the silicon-containing particles is easily uniformly covered with the phosphate compound, and the coverage of the phosphate compound is improved.

[0035] (Phosphate compounds)

[0036] The coating layer containing the phosphate compound has low resistance and good ion conductivity. The phosphate compound can form a P(=O)O - The anions and cations of the structure (also called "PO structure") include metal ions, ammonium ions (NH4 + ) etc. In the PO structure, the bond between P and O may be a single bond (PO), a double bond (P=O), or an intermediate bond. When the covering layer contains a phosphate compound, a peak derived from the PO structure can be observed by X-ray photoelectron spectroscopy (XPS).

[0037] Examples of metals that can form cations in phosphate compounds include alkali metals, beryllium, magnesium, alkaline earth metals, transition metals, and aluminum. Examples of alkali metals include sodium and potassium. Examples of alkaline earth metals include calcium. Examples of transition metals include iron, manganese, and nickel. The phosphate compound may be an inorganic phosphate compound or an organic phosphate compound.

[0038] The covering layer may contain at least one of the following phosphate compounds: a phosphate compound containing one anion and cation represented by the general formula (1); and a phosphate compound containing another anion and cation represented by the general formula (1).

[0039] A in the general formula (1) is an organic group, and the organic group preferably has a structure represented by the formula (2).

[0040]

[0041] In this case, the phosphate compound containing the anion represented by the general formula (1) is etidronate. Examples of etidronate include disodium etidronate (C2H6Na2O7P2) and tetrasodium etidronate (C2H4Na4O7P2).

[0042] Examples of the phosphate compound containing an anion represented by the general formula (1) wherein A in the general formula (1) is an organic group include, in addition to etidronate, clodronate, tedronate, and the like.

[0043] A phosphate compound containing an anion represented by the general formula (1) wherein A in the general formula (1) is an oxygen atom is a pyrophosphate. Examples of pyrophosphates include sodium pyrophosphate (Na4P2O7), potassium pyrophosphate (K4P2O7), calcium pyrophosphate (Ca2P2O7), and iron pyrophosphate (Fe4(P2O7)3).

[0044] The polyphosphate compound includes, for example, at least one selected from the group consisting of tripolyphosphate and tetrapolyphosphate. Examples of tripolyphosphate include sodium tripolyphosphate (Na5P3O 10 ) etc. As tetrapolyphosphate, for example, sodium tetrapolyphosphate (Na6P4O 13 )wait.

[0045] The metaphosphate compound includes, for example, at least one selected from the group consisting of trimetaphosphate and hexametaphosphate. As trimetaphosphate, sodium trimetaphosphate ((NaPO3)3), potassium trimetaphosphate ((KPO3)3), etc. can be listed. As hexametaphosphate, for example, sodium hexametaphosphate ((NaPO3)6), potassium hexametaphosphate ((NaPO3)6), etc. can be listed.

[0046] Among them, the phosphate compound is preferably etidronate from the viewpoint that a soft polymer derived from a phosphate compound is easily formed in the covering layer, and the protective effect of the covering layer on the silicon-containing particles is more firmly maintained during the charge and discharge cycle. Etidronate has many hydroxyl groups and has good affinity with water, and is also preferred from the viewpoint that the dispersibility in water is further improved.

[0047] The amount of phosphate compound covering the surface of the composite particles (hereinafter also referred to as the supported amount of phosphate compound) can be 1 part by mass or more (or 2 parts by mass) relative to 100 parts by mass of the composite particles, can be 1 part by mass or more and 10 parts by mass or less, or can be 5 parts by mass or more and 10 parts by mass or less.

[0048] When the loading amount of the phosphate compound is more than 1 part by mass, the surface of the composite particles can be fully covered with the phosphate compound, and the effect of suppressing side reactions brought by the phosphate compound can be easily obtained. When the loading amount of the phosphate compound is within the range of more than 1 part by mass and less than 10 parts by mass, the larger the loading amount, the easier it is to improve the cycle characteristics. When the loading amount of the phosphate compound is less than 10 parts by mass, it is easy to obtain a negative electrode material (covering layer) with low resistance.

[0049] The amount of the phosphate compound supported (the amount relative to 100 parts by mass of the composite particles) can be determined by the following method.

[0050] The negative electrode material is washed with water to dissolve the phosphate compound. The mass of the phosphate compound dissolved in water is determined by quantitative analysis such as inductively coupled plasma (ICP) emission spectrometry. The mass of the residue that is not dissolved in water is determined as the mass of the composite particles.

[0051] In the case of composite particles containing a silicon compound phase having a conductive layer, the residue not dissolved in water is subjected to quantitative analysis of carbon using a carbon sulfur analyzer or the like. The amount of carbon obtained is derived from the carbon material of the conductive layer. The value obtained by subtracting the mass of carbon obtained by analysis from the mass of the residue not dissolved in water is taken as the mass of the composite particles containing a silicon compound phase.

[0052] The supported amount of the phosphate compound is determined by (mass of the phosphate compound / mass of the composite particles)×100 using the mass of the phosphate compound and the mass of the composite particles determined as described above.

[0053] The thickness of the covering layer is preferably so thin that it does not substantially affect the average particle size of the composite particles. From the viewpoint of protecting the composite particles from the influence of the electrolyte, the thickness of the covering layer is preferably 1 nm or more. From the viewpoint of suppressing the increase in resistance, the thickness of the covering layer is preferably 300 nm or less. The thickness of the covering layer may be less than the thickness of the conductive layer described later. The thickness of the covering layer can be measured by cross-sectional observation of the composite particles using an electron microscope. The electron microscope uses a scanning electron microscope (SEM) or a TEM (transmission electron microscope).

[0054] The phosphate compound on the surface of the negative electrode material can be confirmed by, for example, time-of-flight secondary ion mass spectrometry (TOF-SIMS). Ions derived from the phosphate compound can be detected in the surface layer (including the outermost surface) of the covering layer.

[0055] (Conductive layer)

[0056] From the viewpoint of improving electrical conductivity, at least a portion of the surface of the composite particles may be covered with a conductive layer comprising a conductive carbon material. In this case, a conductive layer may be sandwiched between the composite particles and the covering layer. That is, the covering layer may be formed in the form of a conductive layer covering the surface of the composite particles. The thickness of the conductive layer is preferably so thin that it does not substantially affect the average particle size of the composite particles. From the viewpoint of ensuring electrical conductivity, the thickness of the conductive layer is preferably 1 nm or more. From the viewpoint of suppressing an increase in resistance, the total thickness of the covering layer and the conductive layer is preferably 300 nm or less. The thickness of the conductive layer can be measured in the same manner as in the case of the covering layer.

[0057] The conductive layer is formed by mixing the raw material of the conductive carbon material with the composite particles, firing the mixture, and carbonizing the raw material of the conductive carbon material. As the raw material of the conductive material, for example, coal tar or coal tar tar, petroleum asphalt, phenolic resin, etc. can be used. The mixture of the raw material of the conductive carbon material and the composite particles is fired, for example, in an inert atmosphere (for example, an atmosphere of argon, nitrogen, etc.). The firing temperature is preferably above 450°C and below 1000°C. If within the above temperature range, it is easy to form a conductive layer with high conductivity in the silicate phase with low crystallinity. The firing temperature is preferably above 550°C and below 900°C, and more preferably above 650°C and below 850°C. The firing time is, for example, above 1 hour and below 10 hours.

[0058] (Composite particles)

[0059] The composite particles have a structure in which a silicon phase is dispersed in an ion-conducting phase (matrix). In the composite particles, the stress generated by the expansion and contraction of the silicon phase during charge and discharge is relieved by the ion-conducting phase, and compared with the case where the negative electrode active material is a particle of Si single substance or Si alloy, particle breakage is suppressed, and the reduction in cycle characteristics due to isolation of particles is also suppressed. Therefore, the composite particles can take into account both the high capacity brought about by the inclusion of silicon and the improvement of cycle characteristics.

[0060] The ion-conducting phase may include a silicon compound phase (at least one of a silicate phase and a silicon oxide phase) or a carbon phase. The ion-conducting phase may be composed of a single phase or a plurality of phases.

[0061] The silicon oxide phase is composed of a compound of Si and O. The main component of the silicon oxide phase (for example, 95 to 100% by mass) can be silicon dioxide. The silicate phase is composed of a compound containing a metal element, silicon (Si) and oxygen (O). The silicate phase preferably contains at least lithium silicate. In this case, lithium ions can more easily enter and exit the silicate phase. It should be noted that among the silicon oxide phase and the silicate phase, the silicate phase is preferably used as the main component from the aspect of small irreversible capacity. Here, "main component" refers to a component that accounts for more than 50% by mass of the total mass of the silicon compound phase, and may also account for more than 70% by mass. The ion-conducting phase is composed of a silicon compound phase, and contains a lithium silicate phase as a main component, and may also contain a small amount of silicon oxide phase.

[0062] The composite particles may be composite particles including a silicate phase and a silicon phase dispersed in the silicate phase (composite particles containing a silicate phase). Composite particles containing a silicate phase may be obtained, for example, by pulverizing a mixture of silicate and raw silicon while stirring it with a ball mill or the like, micronizing the mixture, heat-treating the mixture in an inert atmosphere, and pulverizing a sintered product obtained by the heat treatment.

[0063] The silicate phase preferably contains at least one of an alkali metal element (a Group 1 element other than hydrogen in the long period periodic table) and a Group 2 element in the long period periodic table. Alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. Group 2 elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. The silicate phase may further contain rare earth elements such as lanthanum (La), aluminum (Al), boron (B), and other elements.

[0064] Lithium silicate is a silicate containing lithium (Li), silicon (Si) and oxygen (O). The atomic ratio of O to Si in lithium silicate: O / Si is, for example, greater than 2 and less than 4 (z in the formula described below is 0<z<2). When the O / Si ratio is greater than 2 and less than 4, it is advantageous in terms of the stability of the silicate phase and lithium ion conductivity. Preferably, the O / Si ratio is greater than 2 and less than 3. The atomic ratio of Li to Si in lithium silicate: Li / Si is, for example, greater than 0 and less than 4.

[0065] The composition of lithium silicate can be expressed by the formula: Li 2z SiO 2+z (0<z<2). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z preferably satisfies the relationship of 0<z≤1. Examples of lithium silicate include Li2Si2O5 (z=1 / 2) and Li2SiO3 (z=1).

[0066] The average particle size of the fine silicon phase (before the first charge) dispersed in the silicate phase can be less than 500nm, more than 200nm, or less than 50nm. By appropriately miniaturizing the silicon phase in this way, the volume change during charge and discharge becomes smaller, and the structural stability is improved. In addition, the cycle characteristics are improved by making the expansion and contraction of the silicon phase uniform and suppressing particle breakage. The average particle size of the silicon phase is determined by observing the cross section of the negative electrode material using SEM or TEM. Specifically, the maximum diameters of any 100 silicon phases are averaged and calculated.

[0067] The silicon phase dispersed in the silicate phase is a granular phase of silicon (Si) single substance and is composed of a single or multiple crystallites. The crystallite size of the silicon phase can be greater than 5nm and less than 50nm. When the crystallite size of the silicon phase is less than 50nm, the volume change caused by the expansion and contraction of the silicon particles during charging and discharging can be reduced, further improving the cycle characteristics. The crystallite size of the silicon phase can be calculated according to the Scherrer formula from the half-value width of the diffraction peak attributable to the Si (111) plane of the X-ray diffraction (XRD) pattern.

[0068] From the viewpoint of increasing capacity and improving cycle characteristics, the content of the silicon phase in the composite particles containing the silicate phase may be 30% by mass or more and 90% by mass or less, or 35% by mass or more and 75% by mass or less.

[0069] The composition of the composite particles containing a silicate phase can be determined, for example, by the following analysis method.

[0070] <EDX>

[0071] Randomly select 10 composite particles with a maximum diameter of 5 μm or more from the cross-sectional image of the reflected electron image of the negative electrode mixture layer, and perform element mapping analysis based on energy dispersive X-ray (EDX) on each composite particle. Use image analysis software to calculate the area ratio of the element being the object. The observation magnification is expected to be 2000 to 20000 times. Average the measured values ​​of the area ratio of the specified elements contained in the 10 particles. Calculate the content of the element being the object from the obtained average value.

[0072] Desirable measurement conditions for cross-sectional SEM-EDX analysis are shown below.

[0073] <SEM-EDX measurement conditions>

[0074] Processing equipment: JEOL, SM-09010 (Cross Section Polisher)

[0075] Processing conditions: Acceleration voltage 6kV

[0076] Current value: 140μA

[0077] Vacuum degree: 1×10 -3 ~2×10 -3 Pa

[0078] Measuring device: Electron microscope SU-70 manufactured by HITACHI

[0079] Accelerating voltage during analysis: 10kV

[0080] Field: Free Mode

[0081] Probe current mode: Medium

[0082] Probe Current Range: High

[0083] Anode Ap.: 3

[0084] OBJ Ap.:2

[0085] Analysis area: 1μm square

[0086] Analysis software: EDAX Genesis

[0087] CPS: 20500

[0088] Lsec: 50

[0089] Time constant: 3.2

[0090] <AES>

[0091] Randomly select composite particles with a maximum particle diameter of 5 μm or more from the cross-sectional image of the reflected electron image of the negative electrode mixture layer, and use an Auger electron spectroscopy (AES) analyzer (e.g., JAMP-9510F, manufactured by JEOL Ltd.) to perform qualitative and quantitative analysis of the elements on each composite particle. The measurement conditions can be, for example, an acceleration voltage of 10 kV, a beam current of 10 nA, and an analysis area of ​​20 μmφ. The content of the specified element contained in 10 particles is averaged to calculate the content.

[0092] It should be noted that during the charge and discharge process, a coating is formed on the surface of the composite particles due to electrolyte decomposition, etc. In addition, as described below, the composite particles sometimes also have a conductive layer covering the surface of the composite particles. Therefore, the mapping analysis based on EDX or AES is performed in a manner to avoid including a thin coating or a conductive layer within the measurement range, and is performed for a range of 1 μm inward from the peripheral edge of the cross section of the composite particles. Through mapping analysis, the distribution state of the carbon material inside the composite particles can also be confirmed. Since it is difficult to determine the decomposition products of the electrolyte at the end of the cycle, the measurement is preferably performed on samples before or at the beginning of the cycle.

[0093] <ICP>

[0094] The composite particle sample is completely dissolved in a heated acid solution (a mixture of hydrofluoric acid, nitric acid, and sulfuric acid), and the carbon in the solution residue is filtered and removed. The filtrate obtained is then analyzed by inductively coupled plasma emission spectrometry (ICP) to measure the spectral intensity of each element. Next, a calibration curve is prepared using a commercially available standard solution of the element to calculate the content of each element contained in the composite particle.

[0095] The contents of B, Na, K, and Al contained in the silicate phase can be quantitatively analyzed in accordance with JIS R3105 (1995) (Analysis method of borosilicate glass).

[0096] In the composite particles containing a silicate phase, there are a silicate phase and a silicon phase, which can be distinguished and quantified by using Si-NMR. The Si content obtained by the above method is the sum of the amount of Si constituting the silicon phase and the amount of Si in the silicate phase. The amount of Si element contained in the composite particles is distributed in the silicate phase and the silicon phase using the results of the quantitative analysis based on Si-NMR. It should be noted that the standard substance required for quantification can be a mixture of a silicate phase and a silicon phase containing a known Si content in a specified ratio.

[0097] Desirable Si-NMR measurement conditions are shown below.

[0098] <Si-NMR measurement conditions>

[0099] Measuring device: Varian, solid-state nuclear magnetic resonance spectrometer (INOVA-400)

[0100] Probe: Varian 7mm CPMAS-2

[0101] MAS: 4.2kHz

[0102] MAS speed: 4kHz

[0103] Pulse: DD (45° pulse + signal acquisition time 1H decoupling)

[0104] Repeat time: 1200sec~3000sec

[0105] Observation width: 100kHz

[0106] Observation center: around -100ppm

[0107] Signal acquisition time: 0.05 seconds

[0108] Total times: 560

[0109] Sample volume: 207.6 mg

[0110] Hereinafter, an example of a method for producing composite particles containing a silicate phase will be described in detail.

[0111] Step (i) (Step of Obtaining Lithium Silicate)

[0112] The raw material of lithium silicate uses a raw material mixture containing a Si-containing raw material and a Li raw material in a specified ratio. Other elements M may also be included in the raw material mixture as needed. The mixture obtained by mixing the above raw materials in specified amounts is dissolved, and the molten metal is passed through a metal roller to form a thin film to produce lithium silicate. Then, the thin-film silicate is heat-treated in an atmospheric atmosphere at a temperature above the glass transition point and below the melting point to crystallize it. It should be noted that the thin-film silicate can also be used without crystallization. In addition, it is also feasible to manufacture silicate by solid phase reaction instead of dissolving the mixture obtained by mixing in specified amounts and sintering it at a temperature below the melting point.

[0113] Silicon oxide can be used as Si raw material. For example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. can be used as Li raw material. These can be used alone or in combination of two or more. The raw material of element M can include oxides, hydroxides, carbonate compounds, hydrides, nitrates, sulfates, etc. of each element.

[0114] The Si raw material that has not reacted with the Li raw material may remain in the lithium silicate. The remaining Si raw material is dispersed in the lithium silicate in the form of fine crystals of silicon oxide.

[0115] Step (ii) (Step of Obtaining Silicate Composite Particles)

[0116] Next, raw material silicon is mixed with lithium silicate to form a composite. For example, composite particles are produced through the following steps (a) to (c).

[0117] Process (a)

[0118] First, raw silicon powder and lithium silicate powder are mixed at a mass ratio of, for example, 20:80 to 95:5. As the raw silicon, coarse silicon particles having an average particle size of about several μm to several tens of μm may be used.

[0119] Process (b)

[0120] Next, a pulverizing device such as a ball mill is used to pulverize and compound the mixture of raw silicon and lithium silicate while micronizing the mixture. At this time, an organic solvent may be added to the mixture to perform wet pulverization. A predetermined amount of organic solvent may be added to the pulverizing container all at once at the beginning of pulverization, or a predetermined amount of organic solvent may be added to the pulverizing container intermittently in multiple times during the pulverization process. The organic solvent plays a role in preventing the pulverized object from adhering to the inner wall of the pulverizing container.

[0121] As the organic solvent, alcohol, ether, fatty acid, alkane, cycloalkane, silicate, metal alkoxide or the like can be used.

[0122] The raw silicon may be coarse silicon particles having an average particle size of several μm to several tens of μm. The crystallite size of the silicon particles finally obtained, calculated by the Scherrer equation from the half-value width of the diffraction peak attributable to the Si (111) plane in the X-ray diffraction pattern, is preferably controlled to be greater than 5 nm and less than 50 nm.

[0123] It should be noted that the raw silicon and lithium silicate may be micronized and then mixed. In addition, silicon nanoparticles and amorphous lithium silicate nanoparticles may be prepared without using a pulverizing device and then mixed. The nanoparticles may be prepared using a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).

[0124] Process (c)

[0125] Next, the crushed material is sintered while applying pressure by hot pressing or the like to obtain a sintered body. Firing is performed, for example, in an inert atmosphere (for example, an atmosphere such as argon or nitrogen). The sintering temperature is preferably above 450°C and below 1000°C. If it is within the above temperature range, it is easy to disperse tiny silicon particles in the silicate phase with low crystallinity. During sintering, lithium silicate softens and flows as if filling the gaps between silicon particles. As a result, a dense block-shaped sintered body with a silicate phase as a sea and silicon particles as an island can be obtained. The sintering temperature is preferably above 550°C and below 900°C, and more preferably above 650°C and below 850°C. The sintering time is, for example, above 1 hour and below 10 hours.

[0126] When the obtained sintered body is pulverized, silicate composite particles can be obtained. By appropriately selecting the pulverization conditions, silicate composite particles having a predetermined average particle size can be obtained.

[0127] Through the steps (i) and (ii), composite particles having a silicate phase as a matrix and a silicon phase dispersed in the matrix can be obtained.

[0128] The composite particles may also be composite particles including a silicon oxide phase and a silicon phase dispersed in the silicon oxide phase (composite particles containing a silicon oxide phase). The composite particles containing a silicon oxide phase are composed of, for example, SiO x The composite particles containing a silicon oxide phase are obtained, for example, by heat-treating silicon monoxide to separate it into a silicon oxide phase and a fine silicon phase by a disproportionation reaction.

[0129] The composite particles may also be composite particles containing a carbon phase and a silicon phase dispersed in the carbon phase (composite particles containing a carbon phase). The composite particles containing a carbon phase are prepared, for example, by pulverizing a mixture of a carbon source and raw silicon while stirring it with a ball mill or the like to form microparticles, then heat-treating the mixture in an inert atmosphere, and pulverizing the resulting sintered product. Examples of the carbon source include sugars such as carboxymethyl cellulose (CMC), water-soluble resins such as polyvinyl pyrrolidone, petroleum asphalt, coal asphalt, and the like.

[0130] The carbon phase has electrical conductivity, so in the composite particles containing the carbon phase, even if pores are formed around the composite particles, it is easy to maintain the contact points between the composite particles and their surroundings. As a result, it is easy to suppress the reduction in capacity caused by repeated charge and discharge cycles. The carbon phase can be composed of amorphous carbon (i.e., non-crystalline carbon). Amorphous carbon can be hard carbon, soft carbon, or anything else. Amorphous carbon (non-crystalline carbon) generally refers to a carbon material having an average interplanar spacing d002 of the (002) plane measured by X-ray diffraction method exceeding 0.34nm.

[0131] From the viewpoint of increasing capacity and improving cycle characteristics, the content of the silicon phase in the composite particles containing the carbon phase may be 30 mass % to 80 mass % or 40 mass % to 70 mass %.

[0132] The average particle size of the composite particles is, for example, not less than 1 μm and not more than 25 μm, or not less than 4 μm and not more than 15 μm. If it is within the above range, good battery performance is easily obtained. It should be noted that, in this specification, the average particle size refers to: the particle size (volume average particle size) at which the volume cumulative value becomes 50% in the particle size distribution measured by the laser diffraction scattering method. The measuring device can be, for example, "LA-750" manufactured by HORIBA Co., Ltd. Among them, the average particle size of the silicon phase dispersed in the ion conductive phase of the composite particles can be calculated using the above method.

[0133] (Method for producing negative electrode material for secondary battery)

[0134] An example of a method for preparing a negative electrode material for a secondary battery (a method for forming a covering layer) includes a first step of wet mixing a phosphate compound with composite particles and drying. Drying is preferably performed in an inert atmosphere. Through the first step, the phosphate compound is attached to the surface of the composite particles to form a covering layer containing the phosphate compound.

[0135] The wet mixing in the first step can be performed by adding a solvent (dispersion medium) to the phosphate compound and stirring, and then adding the composite particles to the solution (dispersion liquid) of the phosphate compound and stirring. The solvent (dispersion medium) can be water, alcohol, etc., and water is preferred. In this case, it is easy to evenly cover the surface of the composite particles with the phosphate compound.

[0136] The amount of the phosphate compound added may be 1 part by mass or more, or 1 part by mass or more (or 2 parts by mass or more) and 10 parts by mass or less, relative to 100 parts by mass of the composite particles.

[0137] Another example of the method for producing the negative electrode material may include the first step and the following second and third steps. The composite particles to which the phosphate compound is attached obtained in the first step are used as the first intermediate.

[0138] Second step: dry-mixing the first intermediate and the fluororesin. In this way, a second intermediate (silicon-containing particles to which the phosphate compound and the fluororesin are attached) is obtained.

[0139] Step 3: Heat-treating the second intermediate product In this way, a coating layer containing a phosphate compound and a fluororesin is formed on the surface of the silicon-containing particles, in which the phosphate compound is firmly held by the fluororesin.

[0140] The second step and the third step are preferably performed in an inert atmosphere.

[0141] The dry mixing of the second step is performed, for example, using a ball mill. Through the heat treatment of the third step, the fluororesin of the second intermediate is liquefied, and penetrates and diffuses around the composite particles and the particles of the phosphate compound. Thus, the retention of the phosphate compound on the surface of the composite particles is improved. Water is usually used as the dispersion medium of the negative electrode slurry. By having a fluororesin having excellent adhesion and hydrophobicity on the surface of the negative electrode material, the dissolution of the phosphate compound into water is suppressed when preparing the negative electrode slurry.

[0142] Examples of fluororesins include polyvinylidene fluoride (PVDF), polytetrafluoroethylene, and the like. Among these, PVDF is more preferred. In the case of PVDF, it has good adhesiveness and a low melting point, and can form a coating layer at a low heat treatment temperature.

[0143] Figure 1 A cross section of the negative electrode material 20 is schematically shown.

[0144] The negative electrode material 20 includes a composite particle 23 (mother particle) and a covering layer 26 covering the surface of the composite particle 23. The composite particle 23 includes an ion conductive phase 21 and a silicon phase (silicon particle) 22 dispersed in the ion conductive phase 21. The composite particle 23 has a sea island structure in which fine silicon phases 22 are dispersed in the matrix of the ion conductive phase 21. The covering layer 26 contains a phosphate compound. The negative electrode material may include other elements in addition to the composite particle and the covering layer. For example, a conductive layer may be sandwiched between the composite particle and the covering layer.

[0145] (Secondary battery)

[0146] The secondary battery of the embodiment of the present disclosure includes a positive electrode, a negative electrode and an electrolyte. The negative electrode includes the negative electrode material for the secondary battery described above. The negative electrode of the secondary battery and the like are described below.

[0147] [negative electrode]

[0148] The negative electrode contains a negative electrode active material that can absorb and release lithium ions. The negative electrode active material contains the above-mentioned negative electrode material (composite particles). The silicon phase in the composite particles can absorb a large amount of lithium ions, thus contributing to the high capacity of the negative electrode.

[0149] The negative electrode active material may further contain other active material materials. As other active material materials, for example, carbon-based active materials are preferred. The composite particles expand and shrink in volume with charge and discharge. Therefore, if the ratio of the composite particles in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur with charge and discharge. On the other hand, by combining composite particles and carbon-based active materials, while being able to impart a high capacity of the silicon phase to the negative electrode, excellent cycle characteristics can also be achieved. The proportion of composite particles in the total of composite particles and carbon-based active materials can be, for example, 0.5 to 15% by mass, or 1 to 5% by mass. As a result, it is easy to take into account both high capacity and improved cycle characteristics.

[0150] As carbon-based active materials, for example, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be exemplified. Among them, graphite having excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material having a graphite-type crystal structure, for example, including natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon-based active material can be used alone, or two or more can be used in combination.

[0151] The negative electrode, for example, comprises a negative electrode current collector and a negative electrode mixture layer supported on the surface of the negative electrode current collector. The negative electrode mixture layer can be formed by applying a negative electrode slurry formed by dispersing a negative electrode mixture in a dispersion medium to the surface of the negative electrode current collector and drying it. The dried coating film can be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.

[0152] The negative electrode mixture contains a negative electrode active material (the negative electrode material described above) as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as optional components.

[0153] Alternatively, a negative electrode slurry containing a negative electrode active material including composite particles, a phosphate compound, and a binder as required may be applied to the surface of a negative electrode current collector and dried, and rolled as required to form a negative electrode mixture layer. In this way, during the formation of the negative electrode mixture layer, the phosphate compound may be attached to the surface of the composite particles to form a negative electrode material.

[0154] As the negative electrode current collector, a nonporous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, porous body, punched sheet, etc.) is used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. The thickness of the negative electrode current collector is not particularly limited, but from the perspective of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and more preferably 5 to 20 μm.

[0155] Examples of binders include fluororesins, polyolefin resins, polyamide resins, polyimide resins, vinyl resins, styrene-butadiene rubber (SBR), polyacrylic acid and its derivatives. These can be used alone or in combination of two or more. As conductive agents, examples include carbon black, conductive fibers, carbon fluoride, organic conductive materials, etc. These can be used alone or in combination of two or more. As thickeners, examples include carboxymethyl cellulose (CMC), polyvinyl alcohol, etc. These can be used alone or in combination of two or more.

[0156] Examples of the dispersion medium include water, alcohol, ether, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0157] [positive electrode]

[0158] The positive electrode contains a positive electrode active material that can absorb and release lithium ions. For example, a lithium transition metal composite oxide can be used as the positive electrode active material. Examples of lithium transition metal composite oxides include Li a CoO2、Li a NiO2、Li a MnO2、Li a Cob Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn 2-b M b O4, LiMePO4, Li2MePO4F. Here, M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B. Me contains at least a transition element (for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni). Here, 0≤a≤1.2, 0≤b≤0.9, and 2.0≤c≤2.3. It should be noted that the value a representing the molar ratio of lithium increases or decreases according to charge and discharge.

[0159] The positive electrode, for example, comprises a positive electrode current collector and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry formed by dispersing a positive electrode mixture in a dispersion medium to the surface of the positive electrode current collector and drying it. The dried coating film can be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.

[0160] The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, etc. as optional components.

[0161] As the binder and the conductive agent, the same substances as those exemplified in the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can be used.

[0162] The shape and thickness of the positive electrode current collector can be selected from the shape and range of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium.

[0163] [Electrolytes]

[0164] The electrolyte has lithium ion conductivity and may be a liquid electrolyte (electrolyte) or a solid electrolyte.

[0165] As a solid electrolyte, for example, a solid or gel-like polymer electrolyte, an inorganic solid electrolyte, etc. can be used. As an inorganic solid electrolyte, a well-known material in an all-solid-state lithium-ion secondary battery, etc. (for example, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, a halogen-based solid electrolyte, etc.) can be used. The polymer electrolyte, for example, comprises a lithium salt and a matrix polymer, or comprises a non-aqueous solvent, a lithium salt, and a matrix polymer. As a matrix polymer, for example, a polymer material that absorbs a non-aqueous solvent and gels is used. As a polymer material, fluororesins, acrylic resins, polyether resins, etc. can be listed.

[0166] The electrolyte solution contains a solvent and an electrolyte salt. As the solvent, a non-aqueous solvent or water may be used. In the case of a lithium ion secondary battery, the electrolyte salt contains at least a lithium salt.

[0167] The concentration of the lithium salt in the electrolyte is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By controlling the lithium salt concentration within the above range, the ion conductivity is excellent and an electrolyte having a moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0168] As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, etc. are used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be listed. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be listed. As cyclic carboxylic acid esters, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be listed. The non-aqueous solvent can be used alone or in combination of two or more.

[0169] As the lithium salt, for example, a lithium salt containing chloric acid (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorinated acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated imides (LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.

[0170] [Separator]

[0171] It is usually desirable to sandwich a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, for example, polyolefins such as polypropylene and polyethylene can be used.

[0172] As an example of the structure of a secondary battery, an electrode group in which the positive electrode and the negative electrode are wound with a separator and an electrolyte are contained in an outer shell can be cited. Alternatively, instead of a wound electrode group, an electrode group in other forms such as a laminated electrode group in which the positive electrode and the negative electrode are laminated with a separator can be applied. The secondary battery can be, for example, in any form such as a cylindrical, square, coin-shaped, button-shaped, laminated, etc.

[0173] Below, refer to Figure 2 The structure of a rectangular secondary battery as an example of the secondary battery of the present disclosure will be described. Figure 2 This is a schematic perspective view in which a portion of a secondary battery according to an embodiment of the present disclosure is cut away.

[0174] The battery includes a square-bottomed battery case 4, and an electrode group 1 and an electrolyte (not shown) housed in the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, the positive electrode, and the separator around a flat winding core and removing the winding core.

[0175] One end of the negative electrode lead 3 is mounted on the negative electrode collector by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative terminal 6 provided on the sealing plate 5 through a resin insulating plate (not shown). The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is mounted on the positive electrode collector by welding or the like. The other end of the positive electrode lead 2 is connected to the back of the sealing plate 5 through an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive terminal. The insulating plate separates the electrode group 1 from the sealing plate 5, and also separates the negative electrode lead 3 from the battery case 4. The periphery of the sealing plate 5 is fitted with the opening end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed by the sealing plate 5. The injection hole for the electrolyte provided on the sealing plate 5 is blocked by the sealing plug 8.

[0176] "appendix"

[0177] The following techniques are disclosed through the description of the above embodiments.

[0178] (Technology 1)

[0179] A negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles.

[0180] The silicon-containing particles include an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase.

[0181] The coating layer contains at least one phosphate compound selected from the group consisting of phosphate compounds, polyphosphate compounds and metaphosphate compounds containing anions represented by the general formula (1), wherein A is an organic group or an oxygen atom.

[0182] (Technique 2)

[0183] In the negative electrode material for a secondary battery according to technology 1, the ion conductive phase includes at least one selected from the group consisting of a silicate phase, a silicon oxide phase, and a carbon phase.

[0184] (Technique 3)

[0185] The negative electrode material for a secondary battery according to the technique 1 or 2, wherein the organic group is represented by the above formula (2).

[0186] (Technique 4)

[0187] The secondary battery negative electrode material according to any one of techniques 1 to 3, wherein the polyphosphate compound includes at least one selected from the group consisting of tripolyphosphates and tetrapolyphosphates.

[0188] (Technique 5)

[0189] The negative electrode material for a secondary battery according to any one of techniques 1 to 4, wherein the metaphosphate compound includes at least one selected from the group consisting of trimetaphosphates and hexametaphosphates.

[0190] (Technique 6)

[0191] A negative electrode material for a secondary battery according to any one of technologies 1 to 5, wherein the phosphate compound comprises at least one selected from the group consisting of sodium tripolyphosphate, sodium tetrapolyphosphate, sodium trimetaphosphate, sodium hexametaphosphate, potassium trimetaphosphate, potassium hexametaphosphate, disodium etidronate, tetrasodium etidronate, sodium pyrophosphate, potassium pyrophosphate, calcium pyrophosphate and ferric pyrophosphate.

[0192] (Technique 7)

[0193] The negative electrode material for a secondary battery according to any one of techniques 1 to 6, wherein the amount of the phosphate compound attached to the surface of the silicon-containing particles is 1 part by mass or more relative to 100 parts by mass of the silicon-containing particles.

[0194] (Technology 8)

[0195] The negative electrode material for a secondary battery according to any one of techniques 1 to 7, wherein ions derived from the phosphate compound are detected in the surface layer portion of the coating layer by time-of-flight secondary ion mass spectrometry.

[0196] (Technique 9)

[0197] The negative electrode material for a secondary battery according to any one of techniques 1 to 8, wherein a conductive layer containing a conductive carbon material is interposed between the silicon-containing particles and the covering layer.

[0198] (Technology 10)

[0199] A secondary battery comprising a positive electrode, a negative electrode and an electrolyte.

[0200] The negative electrode includes the negative electrode material for a secondary battery according to any one of Techniques 1 to 9.

[0201] [Example]

[0202] Hereinafter, examples of the present disclosure will be described in detail, but the present disclosure is not limited to the following examples.

[0203] 《Secondary batteries A1~A2 and B2~B4》

[0204] (Preparation of composite particles)

[0205] Lithium carbonate (Li2CO3) as a Li raw material and silicon dioxide (SiO2) as a Si raw material are mixed in such a way that the atomic ratio: Si / Li becomes 1.05 to obtain a mixture. The mixture is calcined at 800°C for 10 hours in an inert gas atmosphere to obtain lithium silicate (Li2Si2O5). The obtained lithium silicate is crushed to an average particle size of 10 μm.

[0206] The pulverized lithium silicate and raw silicon (3N, average particle size 10 μm) were mixed at a mass ratio of 40:60. The mixture was filled in a pot (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5). Next, 24 SUS balls (diameter 20 mm) were placed in the pot and the lid was closed, and the mixture was pulverized at 200 rpm for 50 hours in an inert atmosphere.

[0207] Next, the powdered mixture was taken out in an inert atmosphere, and calcined at 600°C for 4 hours under pressure from a hot press in an inert atmosphere to obtain a sintered body of the mixture. The sintered body of the obtained mixture was crushed and passed through a 40 μm mesh to obtain composite particles (composite particles containing a silicate phase). Then, a sieve was used to obtain composite particles with an average particle size of 10 μm.

[0208] The crystallite size of the silicon phase is 15 nm. The silicon phase is granular, and the average particle size of the silicon phase is 20 nm. The main component of the silicate phase is Li2Si2O5, and the content of the silicon phase in the composite particles containing the silicate phase is 60 mass%.

[0209] (Formation of Conductive Layer)

[0210] Then, 100 parts by mass of the composite particles were mixed with 3 parts by mass of coal tar pitch, and the mixture was calcined at 800° C. in an inert atmosphere to cover the surface of the composite particles with conductive carbon. In this way, a conductive layer was formed on the surface of the composite particles containing a silicate phase. The covering amount of the conductive layer was 3% by mass relative to the total of the composite particles and the conductive layer.

[0211] (Manufacturing of negative electrode materials)

[0212] Pure water was added to the powder of the additive shown in Table 1 and stirred for 30 minutes, and then, the composite particles having a conductive layer were further added and stirred for 30 minutes. Then, the mixture was dried at 80°C for 12 hours to remove the water. In this way, composite particles (negative electrode materials) having a covering layer and a conductive layer containing additives were obtained. A high-speed stirrer (made by PRIMIX Corporation) was used as the stirring device. The amount of the additive added was the value shown in Table 1 relative to 100 parts by mass of the composite particles.

[0213] (Production of negative electrode)

[0214] Graphite and negative electrode material were mixed at a mass ratio of 90:10 and used as negative electrode active material. 1 mass part of carboxymethyl cellulose and 1.5 mass parts of styrene-butadiene rubber were added to 97.5 mass parts of negative electrode active material, and a predetermined amount of water was added to prepare negative electrode slurry.

[0215] The negative electrode slurry is applied to both sides of the copper foil as the negative electrode collector, and the coating is dried, rolled, and then cut into a predetermined size to obtain a negative electrode having a negative electrode mixture layer formed on both sides of the negative electrode collector. At this time, a negative electrode collector exposed portion is provided at a part of the negative electrode.

[0216] (Production of positive electrode)

[0217] 2.5 parts by mass of acetylene black and 2.5 parts by mass of polyvinylidene fluoride were added to 95 parts by mass of the positive electrode active material, and then an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode slurry. 0.88 Co 0.09 Al 0.03 A lithium transition metal composite oxide represented by O2.

[0218] The positive electrode slurry is applied to both sides of the aluminum foil as the positive electrode collector, the coating is dried, rolled, and then cut into a predetermined size to obtain a positive electrode having positive electrode mixture layers formed on both sides of the positive electrode collector. At this time, a positive electrode collector exposed portion is provided at a part of the positive electrode.

[0219] (Preparation of Electrolyte)

[0220] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were mixed at a volume ratio of 20:5:75 to obtain a mixed solvent. Lithium hexafluorophosphate was dissolved in the mixed solvent at a concentration of 1 mol / L to prepare an electrolyte solution.

[0221] (Manufacturing of Secondary Batteries)

[0222] An aluminum positive electrode lead is installed on the exposed part of the positive electrode collector of the positive electrode, and a nickel negative electrode lead is installed on the exposed part of the negative electrode collector of the negative electrode. The positive electrode and the negative electrode are spirally wound with a polyolefin separator, and then pressed in the radial direction to make a flat wound electrode body. The electrode body is housed in an outer shell composed of an aluminum laminate, and after injecting the electrolyte, the opening of the outer shell is sealed. In this way, secondary batteries A1~A2, B2~B4, and B6 for evaluation are obtained.

[0223] 《Secondary Battery B1》

[0224] Secondary battery B1 was obtained in the same manner as secondary battery A1 except that a coating layer was not formed on the surface of the composite particles having a conductive layer.

[0225] 《Secondary Battery B5》

[0226] Si single-substance particles (average particle size 10 μm) were used instead of composite particles. No conductive layer was formed on the surface of the Si single-substance particles. In the preparation of the negative electrode material, Si single-substance particles were used instead of composite particles containing a silicate phase having a conductive layer. Secondary battery B5 was obtained in the same manner as secondary battery A1.

[0227] The secondary batteries A1 to A2 and B1 to B5 obtained above were evaluated as follows.

[0228] [Evaluation: Cycle degradation rate]

[0229] In an environment of 25°C, constant current charging was performed at a current of 0.3C until the voltage reached 4.2V, and then constant voltage charging was performed at a voltage of 4.2V until the current reached 0.02C. Then, discharge was performed at a current of 0.5C until the voltage reached 2.5V. This charge and discharge was regarded as one cycle, and 300 cycles were performed.

[0230] The discharge capacity retention rate R (%) was calculated from the following formula using the discharge capacity C1 at the first cycle and the discharge capacity C2 at the 300th cycle.

[0231] Discharge capacity retention rate R = (discharge capacity C2 / discharge capacity C1) × 100

[0232] The obtained discharge capacity retention rate R is used to calculate the cycle degradation rate at 300 cycles according to the following formula. When the cycle degradation rate is small, the cycle characteristics are good. It should be noted that R0 in the formula is the discharge capacity retention rate R of the secondary battery B1 of Comparative Example 1.

[0233] Cycle degradation rate = {(100-R) / (100-R0)}×100

[0234] The evaluation results are shown in Table 1. In Table 1, A1 to A2 are batteries of Examples, and B1 to B5 are batteries of Comparative Examples.

[0235] [Table 1]

[0236]

[0237] Secondary batteries A1 to A2 had a smaller cycle degradation rate than secondary batteries B1 to B5, and thus achieved excellent cycle characteristics.

[0238] 《Secondary Battery B6》

[0239] Secondary battery B6 was obtained in the same manner as secondary battery A1 except that lithium phosphate was used as an additive in the preparation of the negative electrode material.

[0240] The secondary batteries A1, B1, and B6 were evaluated in the same manner as above, and the cycle degradation rate at 350 cycles was determined. C2 in the calculation formula for the discharge capacity retention rate R is the 350th cycle discharge capacity.

[0241] The evaluation results are shown in Table 2. In Table 2, A1 is a battery of an example, and B1 and B6 are batteries of comparative examples.

[0242] [Table 2]

[0243]

[0244] The secondary battery A1 had a smaller cycle degradation rate than the secondary batteries B1 and B6, and thus achieved excellent cycle characteristics.

[0245] 《Secondary batteries C1~C2, D1》

[0246] Composite particles containing a carbon phase are used as the composite particles. Composite particles containing a carbon phase are prepared as follows.

[0247] Coal tar pitch (MCP250 manufactured by JFE Chemical Corporation) as a carbon source and raw silicon (3N, average particle size 10 μm) were mixed at a mass ratio of 50:50. The mixture was filled into a pot (SUS, volume: 500 mL) of a planetary ball mill (P-5 manufactured by Fritsch), 24 SUS balls (diameter 20 mm) were placed in the pot and the lid was closed, and the mixture was pulverized at 200 rpm for 50 hours in an inert atmosphere to obtain a composite of silicon phase and carbon source.

[0248] Next, the composite of the silicon phase and the carbon source is sintered in an inert gas atmosphere to carbonize the carbon source, thereby obtaining a sintered product in which the silicon phase is dispersed in a carbon phase containing amorphous carbon. The sintered product is then pulverized using a jet mill to obtain composite particles containing the carbon phase with an average particle size of 10 μm.

[0249] The crystallite size of the silicon phase was 15 nm. The silicon phase was in a granular form, and the average particle size of the silicon phase was 20 nm. The content of the silicon phase in the composite particles containing the carbon phase was 60 mass %.

[0250] No conductive layer was formed on the surface of the composite particles containing the carbon phase. In the negative electrode material production process, the composite particles containing the carbon phase were used instead of the composite particles containing the silicate phase having the conductive layer. Secondary batteries C1 to C2 were obtained in the same manner as secondary batteries A1 to A2. In addition, secondary battery D1 was produced in the same manner as secondary battery B1 except for the above.

[0251] Each of the secondary batteries obtained above was evaluated in the same manner as above. R0 in the calculation formula of the cycle degradation rate is the discharge capacity retention rate R of the secondary battery D1.

[0252] The evaluation results are shown in Table 3. In Table 3, C1 and C2 are batteries of Examples, and D1 is a battery of Comparative Example.

[0253] [Table 3]

[0254]

[0255] The secondary batteries C1 to C2 had a smaller cycle degradation rate than the secondary battery D1 and obtained excellent cycle characteristics.

[0256] Industrial Applicability

[0257] The secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0258] The present invention has been described with respect to the presently preferred embodiments, but such disclosure is not to be construed in a limiting sense. Various modifications and changes should be apparent to those skilled in the art in the art of the present invention upon reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and changes without departing from the spirit and scope of the present invention.

[0259] Description of Reference Numerals

[0260] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery casing, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: sealing plug, 20: negative electrode material, 21: ion conductive phase, 22: silicon phase, 23: composite particles, 26: covering layer.

Claims

1. A negative electrode material for a secondary battery, comprising silicon-containing particles and a covering layer covering at least a portion of the surface of the silicon-containing particles, The silicon-containing particles include an ion-conducting phase and a silicon phase dispersed in the ion-conducting phase, The coating layer comprises at least one phosphate compound selected from the group consisting of phosphate compounds, polyphosphate compounds and metaphosphate compounds containing an anion represented by the general formula (1), In the general formula (1), A is an organic group or an oxygen atom.

2. The negative electrode material for a secondary battery according to claim 1, wherein The ion conductive phase includes at least one selected from the group consisting of a silicate phase, a silicon oxide phase, and a carbon phase.

3. The negative electrode material for a secondary battery according to claim 1, wherein The organic group is represented by formula (2), 4. The negative electrode material for a secondary battery according to claim 1, wherein The polyphosphate compound includes at least one selected from the group consisting of tripolyphosphates and tetrapolyphosphates.

5. The negative electrode material for a secondary battery according to claim 1, wherein The metaphosphate compound includes at least one selected from the group consisting of trimetaphosphate and hexametaphosphate.

6. The negative electrode material for a secondary battery according to claim 1, wherein The phosphate compound includes at least one selected from the group consisting of sodium tripolyphosphate, sodium tetrapolyphosphate, sodium trimetaphosphate, sodium hexametaphosphate, potassium trimetaphosphate, potassium hexametaphosphate, disodium etidronate, tetrasodium etidronate, sodium pyrophosphate, potassium pyrophosphate, calcium pyrophosphate, and ferric pyrophosphate.

7. The negative electrode material for a secondary battery according to claim 1, wherein The amount of the phosphate compound attached to the surface of the silicon-containing particles is 1 part by mass or more relative to 100 parts by mass of the silicon-containing particles.

8. The negative electrode material for a secondary battery according to claim 1, wherein By time-of-flight secondary ion mass spectrometry, ions derived from the phosphate compound were detected in the surface layer portion of the covering layer.

9. The negative electrode material for a secondary battery according to claim 1, wherein A conductive layer including a conductive carbon material is interposed between the silicon-containing particles and the cover layer.

10. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, The negative electrode comprises the negative electrode material for a secondary battery according to claim 1 .

Citation Information

Patent Citations

  • Negative electrode active substance for secondary battery, and secondary battery

    WO2019151016A1

  • Negative electrode active material for secondary cell, and secondary cell

    WO2019151026A1